Interaction Between Incentive To Expropriate And Investment Opportunities As A Determinant Of Overinvestment Problem In Indonesia - A. Utama, Cynthia; Utama, Sidharta (Asian Academy of Management (AAM), 2016)
The study investigates if the level of investment opportunities reduces the positive impact of expropriation incentive on the level of overinvestments. Under the condition of capital constraint, high incentive of controlling shareholders to expropriate firms’ wealth do not necessarily result in overinvesments if firms have abundant investment opportunities. The study also examine if positive investment-cash flow sensitivity still exists after a significant corporate governance reforms in Indonesia. The study finds no positive relation between investments and cash flow. It documents that overinvestments primarily occur in firms whose controlling shareholders have small ownership. Further, it documents that higher investment opportunities mitigate the effect of expropriaton incentive on overinvestments.